Interventions against child abuse and violence against women Ethics and culture in practice and policy - Hagemann-White, Carol; Kelly, Liz; Meysen, Thomas (Cultural Encounters in Intervention Against Violence, 2019)
This book offers insights and perspectives from a study of "Cultural Encounters in Intervention Against Violence" (CEINAV) in four EU-countries. Seeking a deeper understanding of the underpinnings of intervention practices in Germany, Portugal, Slovenia and the United Kingdom, the team explored variations in institutional structures and traditions of law, policing, and social welfare. Theories of structural inequality and ethics are discussed and translated into practice.